THE ROLE OF SYNBIOTICS IN INCREASING GROWTH AND FEED EFFICIENCY IN CATFISH (Clarias sp.) - Fadil Fadil; Agustina Agustina; Komsanah Sukarti (Universitas Mataram, 2026)
This study aims to examine the effect of synbiotic administration in the form of Lactobacillus plantarum bacteria and sweet potato flour (Ipomoea batatas) in feed on the number of lactic acid bacteria (LAB) in the intestine, growth performance, and feed efficiency in catfish (Clarias sp.). The study used a Completely Randomized Design (CRD) with four treatments and three replications, the treatment given was L. plantarum at a concentration of 108 CFU/mL with a dose of 0.1 mL/g feed combined with sweet potato flour with different doses, namely P0 (without synbiotic), P1 (L. plantarum + 1% sweet potato flour), P2 (L. plantarum + 2% sweet potato flour), and P3 (L. plantarum + 3% sweet potato flour). Catfish measuring 8.45±1.67 cm as many as 120 fish were kept for 30 days in an aquarium with a water volume of 30 L with a density of 10 fish per aquarium. The results showed that the addition of synbiotics did not significantly affect the number of LAB in the intestines of fish (P>0.05) although there was a tendency to be higher than the control. The addition of synbiotics significantly affected the growth performance and feed efficiency of fish (P<0.05). The best treatment was P3 which produced an absolute weight growth of 15.68 g, a specific growth rate of 0.52%/day, and a feed efficiency of 81.18%. Based on this, it can be concluded that the use of L. plantarum synbiotics at a concentration of 108 CFU/mL with a dose of 0.1 mL/g feed and sweet potato flour up to a dose of 3% in feed plays an effective role in increasing growth and feed efficiency in catfish